RURAL DEVELOPMENT AND ITS IMPACT ON ECONOMY (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
India's Rural Development is one of the key factors of India's economic growth. India is primarily an agricultural-based country. Agriculture accounts for about one-fifth of the gross domestic product in India. In order to increase agricultural growth, the Government has developed a number of programs related to rural development in India. The Department of Rural Development in India is the executive body for formulating policies, regulations and actions related to the development of the rural sector. Agriculture, handicrafts, fishing, poultry, and diaries are the main contributors to business and the local economy. The development of rural India has undergone a few changes over the years in its emphasis, methods, strategies and plans. It has taken on a whole new dimension and ideas as a result. Rural development can only be rich and meaningful through customer participation in development. Just as implementation is the backbone of planning, human participation is the backbone of rural development. Human participation is one of the key requirements of the development process both technically and philosophically. For development planners and managers it is important to solicit the participation of different rural groups, to make programs more participatory.